Exploring Students' Perspective about Lectures' teaching strategy to enhance Students' WTC in EFL Classroom - Mega Syafitri; Amra Ariyani; Munir Munir (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study explores the factors influencing students’ Willingness to Communicate (WTC) in English as a Foreign Language (EFL) classrooms and examines teaching strategies that can effectively foster this willingness. Using a qualitative descriptive method, the research was conducted at an EFL Classroom in Indonesia, through classroom observations and in-depth interviews with selected EFL students. The study applies Macintyre et al.’s (1998) heuristic model of WTC as its theoretical foundation. The findings reveal that students’ WTC is shaped by a dynamic interaction of internal, social, and instructional factors. Internally, communicative self-confidence, anxiety levels, and motivation (both instrumental and integrative) played a significant role. Socially, peer support, classroom atmosphere, and fear of negative evaluation were identified as crucial influences. The flexible use of both Bahasa Indonesia and English also helped reduce anxiety and increase participation. Pedagogically, students responded more positively to interactive strategies compared to traditional lectures. Approaches such as cooperative learning, problem-based learning, and project-based learning were found to be the most effective in encouraging active communication, critical thinking, and collaboration. Overall, this research emphasizes that WTC is not fixed, but rather influenced by contextual and emotional readiness. Teachers are encouraged to implement student-centred and emotionally supportive strategies to create a classroom environment where learners feel confident to speak.